Creation of kinetic and verbal image of future engineers-teachers - Stonoha, A. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the problem of the creation of the kinetic and verbal image of future engineers-pedagogues. It is proved that a wholesome cultivated image of an engineer-pedagogue is an integral part of the contents of his her teaching activity. The verbal image is developed only through speech (oral or written). The kinetic image is created on the basis of body language that shows in gestures, postures, facial expressions, distance and mimics. Personal qualities of an engineer-pedagogue affect the results of his her work, which vary depending on special and teaching skills of an engineer-pedagogue and their creative use. The author developed guidelines for a future engineer-pedagogue aimed at promoting his her positive verbal image, for example, such suggestions as to converse and not just talk, to use the technique of the correspondence dialogue and the technique of the active use of words, to say what people expect to hear, to provoke a smile, to overcome social taboos, to emphasize key words, to change the tone. The paper also acquaints readers with guidelines for the development of the kinetic image.